Development and Validity of the Fear of Water Assessment Questionnaire - Misimi, Fatmir; Kajtna, Tanja; Misimi, Samir; Kapus, Jernej (Frontiers in Psychology, 2020)
Fear of water is the strongest predictor for no or low swimming competencies. Some individuals will never learn to swim due to their complete avoidance of water, whereas other might have difficulty with learning due to the fact that they cannot sufficiently relax their body to facilitate floating or swimming. Therefore, it is important to identify them and to establish effective teaching strategies that can best help this specific population. Recognizing this, there is a clear need for an assessment tool, which can help swim teachers and coaches identify people with a fear of water. The aim of this study was to develop and validate a fear of water assessment questionnaire (FWAQ). Following a process of item creation and exculpation, a 40-item questionnaire was completed by 2,074 developing male and female participants from the general population. Exploratory factor analysis was conducted to identify any underpinning latent factor structures, resulting in a 20-item, 3-factor solution that accounted for 31.69 % of the explained variance, with an overall reliability of Cronbach alpha α = 0.831. A subsequent discriminant function analysis was conducted and the questionnaire was able to correctly classify 98.2 % of participants. We concluded that the findings from this study support that the FWAQ is a valid scale that effectively measures the fear of water.